Strategic Management of Regional Disparities: Human Development Analysis of the Madura Islands Using GMM - Gunawan, Gunawan; Ilyas, Muh. Fadhel G Bata; Azizurrohman, Muhammad (Universitas Muhammadiyah Yogyakarta, 2026)
This study analyzes the factors influencing the Human Development Index (HDI) in the Madura Islands, focusing on the impacts of poverty, unemployment, household consumption expenditure, and Gross Regional Domestic Product (GRDP). The research employs a dynamic panel data model and the Generalized Method of Moments (GMM) using data from 2012 to 2021. This approach examines both short-term and long-term effects of the selected economic and social variables on HDI. Findings reveal that the previous year's HDI positively influences the current year's HDI, indicating strong persistence. High poverty and unemployment levels significantly negatively affect HDI, while household consumption expenditure is not significant. GRDP positively impacts HDI in the long term. Surprisingly, unemployment shows a short-term positive effect, suggesting the role of targeted social interventions. The study supports theories of cumulative causation and emphasizes the need for inclusive growth strategies. It provides valuable policy insights to enhance human development and address regional disparities in the Madura Islands. The results underscore the importance of sustained economic growth, high-quality public services, and targeted poverty-alleviation and employment policies.